Pengaruh Website Design Quality dan E-Service Quality Terhadap Repurchase Intention Sociolla E-Trust Sebagai Variabel Mediasi - Wuisan, Dewi S.S; Candra, David; Tanaya, Maisie Adeline; Natalia, Velliana; Bernarto, Innocentius (Computatio : Journal of Computer Science and Information Systems, 2020)
This study aims to examine the positive influence of website design quality and e-service quality on repurchase intention. The sampling technique in this study uses a non-probability sampling technique that is purposive sampling. The target population is all Sociolla customers in the Jakarta and Tangerang regions. The number of samples in this study were 200 respondents. The method of collecting data is questionnaire or questionnaire. Data were processed using Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis with the help of SmartPLS software. The results showed that the variable website design quality has a positive effect both directly and indirectly on repurchase intention mediated by e-trust, while the e-service quality variable has no direct effect but has an indirect effect on repurchase intention mediated by etrust.AbstrakPenelitian ini bertujuan untuk menguji pengaruh positif website design quality dan e-service quality terhadap repurchase intention. Teknik pengambilan sampel pada penelitian ini menggunakan teknik non-probability sampling yaitu purposive sampling. Target populasi adalah semua pelanggan Sociolla di wilayah Jakarta dan Tangerang. Jumlah sampel dalam penelitian ini sebesar 200 responden. Metode pengumpulan data dengan angket atau kuesioner. Data diolah dengan menggunakan analisis Partial Least Square - Structural Equation Modeling (PLS-SEM) dengan bantuan software SmartPLS. Hasil penelitian menunjukkan bahwa variabel website design quality memiliki pengaruh positif baik secara langsung maupun tidak langsung terhadap repurchase intention dimediasi oleh e-trust, sedangkan variabel e-service quality tidak memiliki pengaruh secara langsung namun memiliki pengaruh secara tidak langsung terhadap repurchase intention dimediasi oleh e-trust.